Protein profiles of CCL5, HPGDS, and NPSR1 in plasma reveal association with childhood asthma. Issue 9 (25th May 2016) - Hamsten, C.; Häggmark, A.; Grundström, J.; Mikus, M.; Lindskog, C.; Konradsen, J. R.; Eklund, A.; Pershagen, G.; Wickman, M.; Grunewald, J.; Melén, E.; Hedlin, G.; et al.
Abstract: Asthma is a common chronic childhood disease with many different phenotypes that need to be identified. We analyzed a broad range of plasma proteins in children with well‐characterized asthma phenotypes to identify potential markers of childhood asthma. Using an affinity proteomics approach, plasma levels of 362 proteins covered by antibodies from the Human Protein Atlas were investigated in a total of 154 children with persistent or intermittent asthma and controls. After screening, chemokine ligand 5 (CCL5) hematopoietic prostaglandin D synthase (HPGDS) and neuropeptide S receptor 1 (NPSR1) were selected for further investigation. Significantly lower levels of both CCL5 and HPGDS were found in children with persistent asthma, while NPSR1 was found at higher levels in children with mild intermittent asthma compared to healthy controls. In addition, the protein levels were investigated in another respiratory disease, sarcoidosis, showing significantly higher NPSR1 levels in sera from sarcoidosis patients compared to healthy controls. Immunohistochemical staining of healthy tissues revealed high cytoplasmic expression of HPGDS in mast cells, present in stroma of both airway epithelia, lung as well as in other organs. High expression of NPSR1 was observed in neuroendocrine tissues, while no expression was observed in airway epithelia or lung. In conclusion, we have utilized a broad‐scaled affinity proteomics approach to identify three proteins with altered plasma levels in asthmatic children, representing one of the first evaluations of HPGDS and NPSR1 protein levels in plasma.